Treatment for recurrent HCV infection after liver transplantation for final stages of chronic hepatitis С - V. E. Syutkin; O. I. Andreitseva; A. V. Kozlova (Трансплантология (Москва), 2018)
The review discusses whether antiviral therapy for recurrent hepatitis C virus (HCV) infection may be used following liver transplantation. It analyzes the concepts of pre-emptive therapy initiated within the first weeks after the transplantation, as well as therapy for histologically verified active hepatitis and/or liver fibrosis. Capabilities and limits in the use of pegylated interferons and ribavirin as monotherapy or combination therapy are considered. Particular emphasis is placed on the role of viral kinetics in the determination of the duration of further therapy, including the possibility of its prolongation up to > 12 months. There are arguments in favor of a better course of recurrent HCV infection in patients receiving cyclosporine versus those taking tacrolimus.